Maritime Terrorism Network: Threat and Security in Contemporary Southeast Asia - Herdi Sahrasad; Al Chaidar; M. Akmal; Saifullah Ali; Nanda Amalia; Dara Quthni Effida (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2018)
Southeast Asia is a region that is vulnerable to terrorism. Of the total terrorism cases that occurred in the world, 50 percents occurred in this region. Mindanao is one of the regions in Southeast Asia that since a long time ago has been the basis of world-class terrorism. This situation is getting worse due to the presence of terrorist groups with a strong tradition of maritime piracy. The nexus between terrorism and piracy makes the issue of maritime terrorism in Southeast Asia a regional security concern. Abu Sayyaf Group is a terrorist group in the Southern Philippines that is very well-known but difficult to map. This makes the Abu Sayyaf a source of prolonged tension in the Southern Philippines in particular and in the Southeast Asia region in general. This study is a field observation that uses descriptive analysis to reveal the details of the Abu Sayyaf and the issue of terrorism in Mindanao.